Experimental Study on Behaviour of Reinforced Concrete-Bubbled Beam - Shubham S. Zanwar; Sandeep B. Javheri; Mahesh G. Kalyanshetti (Architecture Image Studies Scientific Journal)
The construction industry constantly seeks innovative solutions to improve the efficiency and sustainability of building structures. One such advancement is the Bubble Deck Beam, which revolutionizes conventional beam design by incorporating air-filled plastic spheres into reinforced concrete beams. This study investigates the effect on displacement and flexural strength after introducing voids in beam by addition of HDPE balls in different numbers for different amount of volumetric reduction. Beams of size 150mm x 200mm x 1200mm were casted having concrete grade M25. Three number of beams were casted each for conventional beam with zero concrete replacement, BB1 having 2% volumetric reduction, BB2 having 4% volumetric reduction. BB3 having 6% volumetric reduction. BB4 having 8% volumetric reduction. The casted beams are cured for 28 days then this beam were tested for flexural strength. Simply supported beam with two equal point load acting at top surface of beam will be tested up to failure in well-equipped heavy structural laboratory. The behaviour of beam studied in concern with crack and ultimate load. Experimental findings suggest that 2% volumetric reduction is more optimal in usage.